EFFECTIVE METHODS OF TEACHING ENGLISH TO CADETS (International Conference on Economics, Finance, Banking and Management, 2025)
This article explores the most effective methods of teaching English to cadets, with a focus on military education contexts. It highlights the significance of communicative competence, professional vocabulary, and discipline-specific language skills required for cadets' future roles. The study draws on existing literature, outlines practical teaching methods tailored to cadet needs, and presents findings from recent educational experiments. Recommendations are provided for optimizing English language instruction in military institutions.